The effect of local crime on well-being: Evidence for Germany - Christian Krekel; Marie Luise Poprawe (ETH Zurich, KOF Swiss Economic Institute, 2014)
This paper investigates the effect of local crime on well-being in Germany, using data from the German Socio-Economic Panel (SOEP) and a novel data set constructed from official police crime statistics, covering both counties and urban districts for the time period between 1994 and 2012. We find that local area crime has a signi cantly negative impact on life satisfaction, makes residents worry more frequently, and worry more about crime in Germany. In particular, a 1% increase in the crime frequency ratio results in a 0.043 standard deviation decrease in life satisfaction. This effect is driven almost exclusively by violent crimes, while property crimes and other crimes have no significant impact on well-being.
Keywords: I31; K42; R50; 330; Crime; Well-Being; Germany